AKTIVITAS PENGHAMBATAN ENZIM PROTEASE 6LU7 VIRUS SARS-COV-2OLEH SENYAWA FLAVONOID DARI TUMBUHAN GENUS ARTOCARPUS SECARA IN SILICO - Adiansyah Adiansyah; Dumartina Hutauruk; Lastry Derliana Nainggolan (UNIVERSITAS SARI MUTIARA INDONESIA, 2021)
The genus Artocarpus is one of the genera of Moraceae plants, this genus consists of 50 species and 40 species of them are found in Indonesia. Several studies have reported that the flavonoid compounds contained in the genus Artocarpus have cytotoxic, antiproliferative, antimalarial, anti-inflammatory, and antioxidant properties. The purpose of this study was to determine the inhibitory activity of the protease enzyme 6LU7 of the SARS-COV-2 virus by flavonoid compounds from plants of the genus Artocarpus using the in-silico tethering method. The method used in the in-silico tethering process is carried out using the PLANTS program, validated using the Yasara program, and visualized using the Moe2008 program. The protein model of the 6LU7 Protease Enzyme was downloaded via the Protein Data Bank (PDB) with the code 6LU7. The results of this study indicate that the binding of flavonoid compounds from the genus Artocarpus to the expression of 6LU7 gives valid results in silico. The flavonoid compounds of the Artocarpus genus inhibited the 6LU7 enzyme protein with a higher docking value than each of the comparison drugs and produced 7 amino acid residues that were bound to each other. The conclusion of this study can be concluded that flavonoid compounds from the genus Artocarpus inhibit the expression of 6LU7 protein with a docking score close to the docking score of each comparison drug and 7 amino acid residues are bound to each other.